2013
DOI: 10.1186/1756-6649-13-5
|View full text |Cite
|
Sign up to set email alerts
|

Validity of actigraphs uniaxial and triaxial accelerometers for assessment of physical activity in adults in laboratory conditions

Abstract: BackgroundFew studies to date have directly compared the Actigraphs GT1M and the GT3X, it would be of tremendous value to know if these accelerometers give similar information about intensities of PA. Knowing if output is similar would have implications for cross-examination of studies. The purpose of the study was to assess the validity of the GT1M and the GT3X Actigraph accelerometers for the assessment of physical activity against oxygen consumption in laboratory conditions.MethodsForty-two college-aged par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
144
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(155 citation statements)
references
References 40 publications
9
144
1
1
Order By: Relevance
“…Systematic and random measurement errors may lead to misleading results, both when documenting time spent sedentary and in physical activity and when determining associations with relevant outcomes such as health and well-being. As an alternative, objective measurements using accelerometers offer accurate information of time spent sedentary and in physical activity (18,19). Thus, accelerometer recordings have been used as the gold standard for validating questionnaire-based data on time spent sedentary and in physical activity (20,21).…”
mentioning
confidence: 99%
“…Systematic and random measurement errors may lead to misleading results, both when documenting time spent sedentary and in physical activity and when determining associations with relevant outcomes such as health and well-being. As an alternative, objective measurements using accelerometers offer accurate information of time spent sedentary and in physical activity (18,19). Thus, accelerometer recordings have been used as the gold standard for validating questionnaire-based data on time spent sedentary and in physical activity (20,21).…”
mentioning
confidence: 99%
“…The criterion validity of the CHAMPS questionnaire to estimate the amount of PA performed was contrasted with the help of the accelerometer ActiGraph GT3X (ActiGraph, LLC, Pensacola, FL, USA), an instrument that has been considered appropriate for these purposes 16 . In the present study, accelerations were registered with a sample frequency of 100 Hz and then filtered, digitalized, and compiled in periods of 60 seconds.…”
mentioning
confidence: 99%
“…Similarly, Kozey-Keadle et al [33] also concluded that while measuring activities related to sedentary life style behavior the researchers should prefer activPAL as it was more sensitive and reliable in quantifying the physical activities during sedentary life style. Kelly et al identified the validity of two different generations of ActiGraph (Uni and Triaxial) and concluded that both generations of ActiGraph had accuracy of 88.11% when compared to oxygen consumption (laboratory based standard protocol [31]. Kelly conducted a study on young adult participants and employed two generations of actiGraph for measuring a physical activity [31].…”
Section: Discussionmentioning
confidence: 99%
“…Kelly et al identified the validity of two different generations of ActiGraph (Uni and Triaxial) and concluded that both generations of ActiGraph had accuracy of 88.11% when compared to oxygen consumption (laboratory based standard protocol [31]. Kelly conducted a study on young adult participants and employed two generations of actiGraph for measuring a physical activity [31]. An interesting study to determine the optimal placement of accelerometers in determining the Physical Activities was performed by Cleland et al in 2013, according to Ian Cleland study hip worn accelerometers had highest performance index in measuring physical activity 0.978 followed by thigh worn accelerometers 0.971 [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation